Digital Emotional Intelligence: Transforming Emotional Intelligence in Shaping Digital Empathic Leadership - Asri fianti Asmar; Umi Narimawati; Bobi Kurniawan (Green Publisher Indonesia, 2026)
The world is currently experiencing accelerated digitalization, a transformation that is changing the culture of work, communication, and leadership. Consequently, the emotional touch in leadership is slowly declining. Many leaders possess technical digital acumen, but fail to build emotional bonds in the digital space, often resulting in a rigid work culture that leads to misunderstandings in coordination. Conversely, conventional leadership, which relies on physical presence, is now experiencing disorientation. Leaders who are emotionally intelligent in the real world are not necessarily able to manifest that empathy through digital platforms. This research examined how a leader can validate emotions without physical presence and detect emotional distress in the team through digital communication patterns. The aim of this research is to formulate a leadership model, Digital Emotional Intelligence, as a transformation of emotional intelligence, an absolute prerequisite for empathetic leadership in the digital era. Using a qualitative comparative case study method, data were collected through literature study on Travis Kalanick (Uber) and Mark Zuckerberg (Meta) and analyzed based on Goleman's emotional intelligence theory. The findings reveal that Kalanick failed to transform his emotional intelligence, leading to his downfall, while Zuckerberg successfully transformed by admitting mistakes and recruiting high-EQ leaders. This study formulates DEQ as the blend of traditional and modern skills in the digital era, recommending a paradigm shift from Digital Command to Digital Connection, with practical applications including empathetic grammar, emojis in virtual chats, and emotionally-attuned performance assessments.